Oxigenoterapia hiperbárica para instalação de implantes dentários em pacientes irradiados: revisão sistemática e metanálise - Condezo, Anthony Froy Benites (2018)
The survival rate of dental implants, installed in cancer patients, may be influenced by the immediate and late effects of radiotherapy. Hyperbaric Oxygen Therapy (OHB) is considered an adjunct to the installation of implants, since it provides beneficial effects on wound healing through angiogenesis, due to the increase in oxygen tension. However, it is still controversial to prove its efficacy in irradiated patients. Therefore, the objective of this study was to perform a systematic review with meta-analysis, in order to reveal if hyperbaric oxygen therapy influences the survival of dental implants installed in irradiated patients and, consequently, advise the surgeon on the use of OHB as an adjuvant in surgery of implants. A search was made for relevant studies published in the English language using the following databases: PubMed / Medline, Science Direct, Embase and Cochrane Library, between January 1985 and July 2018. The research followed the standards and the PRISMA statement and the systematic review was duly recorded in the PROSPERO database. The inclusion and exclusion criteria were applied and all articles were selected considering the PICO questions. The research in the database resulted in 72 studies, 9 of which were selected using the eligibility criteria, and based on the abstracts. Finally, the eligibility and quality assessment process resulted in 3 studies for statistical analysis. The quality of each included study was assessed using the National Council of Health and Medical Research of Australia (NHMRC). An analysis was performed to determine if OHB decreases the risk of failure of the dental implant. According to the survival rate, there was no evidence that the risk of one implant failing is different between the group case and controle. Considering the number of implant failures, there was no evidence that the risk of implant failure is different between patients who were and were not submitted to OHB. In addition, the risk of an implant failure did not depend on the anatomical site. From this study, it can be affirmed that there are few scientific papers that answer the questioning of this study, so more detailed clinical studies are necessary to be able to conclude about this.